Analysis of ferroptosis-associated genes in Crohn’s disease based on bioinformatics - Ji, Xingyu; Ma, Su; Sun, Xiaomei; Yu, Dan; Song, Ye; Li, Rui (Frontiers in Medicine, 2023)
Background Ferroptosis, a novel mode of apoptosis has recently been shown to be associated with fibrosis, tumor, cardiovascular, and other diseases. In this study, using bioinformatic analysis, we identified ferroptosis genes associated with Crohn’s disease (CD) and performed biological function analysis, identified potential drug targets, and provided new directions for the future treatment of CD. Methods Differential expression analysis was performed using the GSE186582 dataset from the Gene Expression Omnibus (GEO) database. Ferroptosis-associated genes were downloaded from the FerrDB database, and overlapping genes associated with CD and ferroptosis were extracted. Then, we performed functional enrichment analysis, constructed a protein-protein interaction network (PPI), identified the correlation between hub genes and immune infiltration, performed external validation using a second and third dataset (GSE102133, GSE95095), and identified potential therapeutic agents. Finally, we validated the protein expression levels of the identified hub genes by immunohistochemical staining in the colon tissues from CD and healthy participants. Results A total of 28 ferroptosis-associated genes associated with CD were identified in our analysis, which included 22 up-regulated and 6 down-regulated genes. Gene Ontology (GO) analysis showed that these genes are essential for the apical plasma membrane and amide transport, and Metascape analysis showed that these genes mainly act on IL-4 and IL-13 signaling pathways. Five hub genes, PTGS2, IL6, IL1B, NOS2, and IDO1, were identified by a protein interaction network, and external validation of these hub genes showed statistically significant differences in expression between the CD patients and normal participants (p < 0.05), and all AUC values were greater than 0.8. Further, we predicted the top 10 drugs used to treat CD. Immune infiltration results suggest that Hub gene is related to T cells, macrophages, dendritic cells, and other immune cells. Finally, the results of immunohistochemical experiments showed that the protein expression of the hub gene was higher in CD colon tissue than in normal subjects (p < 0.05). Conclusion Bioinformatics analysis showed that ferroptosis is closely related to the development of CD, and the prediction of potential drugs provides new targets for the treatment of CD. Moreover, five hub genes identified are potentially new and effective markers for the diagnosis of CD.